Development of an individually customizable integral carbon aerobar based on sEMG measurements of the upper limbs - Wurnitsch, W.; Siebert, M.; Litzenberger, S.; Sabo, A. (Procedia Engineering, 2010)
The aim of this project is the development of an individually customizable integral carbon aerobar with reduced weight and optimized aerodynamics. After the introduction, which includes a short historical overview as well as an explanation of materialcharacteristics the work continues with a preliminary study of the effect on different aerobar positions on significant upper body muscle activities with surface electromyography measurements. A maximal adjustable test handlebar permits variability to fit the handlebar in all directions to the athlete. The subject has the possibility to do test-runs on the track in the adjusted position. The bike will be equipped with a power crankset from Schoberer Rad Messtechnik (SRM) to analyse the power output which is-given a constant speed-related to the drag on the rider. All dimensions of the adjustable testbar were captured. The aerobar was designed with Dassault Systemes CATIA V5 and dimensioned with ANSYS.